Lateral Design Value (Z) for Various Double Shear Multi-Nailed Wood Connections with Steel Side Plates - Sucahyo Sadiyo (Masyarakat Peneliti Kayu Indonesia, 2010)
Experiments were conducted to analyze the lateral design value (Z) for double shear wood connections using multiple nails with steel side plates of seven different Indonesian tropical wood species under uniaxial compression loading. Results showed variations in average wood moisture content (MC) for nail connections, the lowest in Kempas to the highest in Bornean Super wood. Whereas for average specific gravity (SG), density (ρ), allowable load compressive stress parallel to grain (Ftk//) and tensile stress parallel to grain (Ftr//), the lowest was in Meranti merah and highest in Bangkirai wood. Values for Ftk//, Ftr// and Z tent to be proportional to the wood’s SG or ρ. Ftr// values were 1.5 to 2 times higher than Ftk//. Pattern or parallel line distribution of average Z values among the experiments was relatively similar. The highest Z value was obtained by 5.2 mm nail followed by 5.5 mm nail for all experiments, except experiment-I (theoretical) and experiment II-B (EC5 2007). Generally, the number of nails did not provide significant effect (relatively uniform) on the average Z value double shear connections.